Contribution of Agility and Speed to Dribbling Ability of Futsal Players Sman 10 Bengkulu City - Dewa, Feby Indra; Sumantri, Ajis; Martiani, Martiani (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to determine the contribution of agility and speed to the dribbling ability of SMA Negeri 10 Bengkulu City futsal players. correlation or correlational research is research that seeks to determine whether there is a relationship between 3 or more variables. independent variables, namely agility and speed with the dependent variable, namely dribbling ability. The type of sempel in this study using total sampling technique. The sempel is all SMA Negeri 10 Bengkulu city futsal players totaling 15 people. The instruments used in this study were tests of agility, speed and dribbling ability. The agility test and dribbling ability obtained rtable of 0.514 because the correlation coefficient between rxy = 0.95> 0.514 and a contribution of 90%. And the speed and dribbling ability test obtained an rtable of 0.514 because the correlation coefficient between rxy = 0.90> 0.514 and a contribution of 81%, which means that the contribution of agility and speed to the dribbling ability of SMA Negeri 10 Bengkulu City futsal players is significant and large. Thus the hypothesis that reads